Cross-cultural differences in autistic traits and the level of psychological distress - Fani, Omidreza (2024)
This thesis explores the intricate relationship between autism, cultural influences, and mental health outcomes, with a focus on cross-cultural variations in the perception of autistic traits and well-being of parents raising autistic children. Autism is characterized by challenges in social interaction, communication, and repetitive behaviours, and its diagnosis relies on the interpretation of social behaviour, which is culturally influenced. Culture is shaping norms and beliefs about behaviours. Hence, the cultural lens potentially affects the interpretation of autistic traits, affecting diagnosis and support systems. The research aims to shed light on how different cultures perceive autistic traits, their understanding of autism, and the resulting impact on parental mental health. Four comprehensive studies are presented in this thesis, exploring cross-cultural disparities, investigating influential cultural factors, and understanding parental distress across different cultural contexts.